Effects of sheep manure in agricultural soils on the behavior of folsomia candida and initial growth and development of avena sativa Efeitos do esterco de ovelha em solos agrícolas no comportamento de folsomia candida e no crescimento e desenvolvimento inicial de avena sativa - Zortea T. (2021)
© 2021, Instituto Internacional de Ecologia. All rights reserved.The aim of this study was to evaluate the effects of sheep manure in agricultural soils on the behavior of Folsomia candida and initial growth and development of Avena sativa. For this, an Oxisol was submitted to different doses of sheep manure and was subsequently evaluated for Folsomia candida survival and avoidance behavior through standardized ecotoxicological assays, the initial performance of oats by germination test and the soil basal respiration rate by respirometry methodology. There was an increase in the basal respiration rate of the soil by the application of sheep manure and this was consistent with the increase of the doses. The survival rate and avoidance behavior of springtails were not altered and there was no change in the initial performance of oats, indicating that this manure can be used for organic fertilization of soils with low soil pollutant potential.